2015
DOI: 10.1063/1.4930164
|View full text |Cite
|
Sign up to set email alerts
|

Active terahertz device based on optically controlled organometal halide perovskite

Abstract: An active all-optical high-efficiency broadband terahertz device based on an organometal halide perovskite (CH3NH3PbI3, MAPbI3)/inorganic (Si) structure is investigated. Spectrally broadband modulation of the THz transmission is obtained in the frequency range from 0.2 to 2.6 THz, and a modulation depth of nearly 100% can be achieved with a low-level photoexcitation power (∼0.4 W/cm2). Both THz transmission and reflection were suppressed in the MAPbI3/Si structure by an external continuous-wave (CW) laser. Enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…We took note that the measurement of the THz modulation with hybrid perovskite/Si devices at the wavelength of 532 nm has never been reported even with the fact that green light is the most abundant spectral component in sunlight. So, in contrast to previous research on perovskite-based modulators with weak THz pulse and 400-nm optical pump22, we chose 532 nm of wavelength as optical pump and modulated intense THz pulse, which will be the realistic tool to characterize perovskite materials as solar devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took note that the measurement of the THz modulation with hybrid perovskite/Si devices at the wavelength of 532 nm has never been reported even with the fact that green light is the most abundant spectral component in sunlight. So, in contrast to previous research on perovskite-based modulators with weak THz pulse and 400-nm optical pump22, we chose 532 nm of wavelength as optical pump and modulated intense THz pulse, which will be the realistic tool to characterize perovskite materials as solar devices.…”
Section: Resultsmentioning
confidence: 99%
“…One recent report has shown an optically controlled THz amplitude modulator based on the hybrid structure of Si with a perovskite film fabricated via two-step solution processing22. However, the instability of perovskites under ambient conditions has remained problematic in practical applications23.…”
mentioning
confidence: 99%
“…Many other materials showing dynamic THz responses applicable to active THz modulation also exist, such as NbO 2 , [211] InSb, [212,213] QWs, [214] titanium oxides, [215] orthoferrites, [216][217][218] rare-earth nickelates, [219][220][221] manganites, [222][223][224] topological insulators, [225][226][227] multiferroics, [228] molecular crystals, [229,230] medicines, [231] polymers, [232][233][234][235][236][237][238] and halide perovskites, [239][240][241][242][243][244][245][246] to name but a few. Considering the diversity of the material properties and the control mechanisms, plasmonic hybridization may bring about new possibilities for a wide variety of active THz devices.…”
Section: Potential Candidatesmentioning
confidence: 99%
“…THz waves can be modulated by optically pumping silicon to form a temporary region with either high absorption or strong reflection [9]. As a result, Okada et al [10] and Xie et al [11] proposed silicon-based spatial THz modulators (STM), while Zhang et al [12] and Cheng et al [13] reported optically controlled reconfigurable quasi-optical THz devices. Optically tunable THz modulators enable broadband modulation with considerable modulation depth.…”
Section: Introductionmentioning
confidence: 99%